The Strategic Plan Evaluation of X Hospital in 2016-2021 - Alif Khoiruddin Azizi (Universitas Muhammadiyah Yogyakarta, 2017)
X Hospital has conducted the strategic plan and evaluated it, but there is inexpediency of work program and the budget sets in its implementation. Therefore, the goal of the strategic plan is not achieved and the unit performance is not maximal. Consequently, this study is aimed to analyze the process of the arrangement to the implementation of the Strategic Plan policy and the influencing factors. This research uses qualitative method. The primary data collection is conducted in-depth interview to 14 informants, while that of secondary data are obtained by reviewing the documents. The results show that the process of arranging and evaluating the strategic plan and the work program has not fully involved all the Directors and Managers concerned. Furthermore, the clarity and consistency of the Strategic Plan still lacks of the stage of implementation. The corporate performance-level parameters based on the balanced score card are not also descended to the Key Performance Indicator per directorate. However, the aspect of Human Resource understanding to the Strategic Plan has been fulfilled. Aspects of attitude and commitment both to the Executive Officers, Board of Directors and Managers are also very well.